Pengaruh Model Cooperative Integrated Reading and Compotition terhadap Kemampuan Menulis Teks Argumentasi Kelas V SD - Utami, Dinny Salfiyah; Helvia, Nelda; Chandra, Chandra; Wijanarko, Tiok (Asian Journal of Early Childhood and Elementary Education, 2024)
The aim of this research is to improve learning outcomes for writing argumentative texts through the application of the Cooperative Integrated Reading and Compotition (CIRC) model for fifth grade elementary school students and to describe the obstacles and solutions for implementing the CIRC model in improving Indonesian language learning outcomes in writing argumentative texts. The main research method used was qualitative methods which were carried out during one meeting. The subjects of this research were class V students. The data collection techniques used were observation and analysis of argumentative texts produced by students. The research results show that the CIRC model shows a significant interaction with students' critical thinking abilities in its influence on their ability to write argumentative texts. These results show that the CIRC model can significantly improve students' ability to write argumentative texts, both for students who have high and low critical thinking abilities.